Educação financeira: desafios de nosso tempo - Silva, Romildo Almeida da (2019)
The present work had the objective propose activities that may stimulate reflections about financial habits and awareness of consumption in students from a ninth grade class of Padre Anchieta State School in Duque de Caxias/RJ. As a consequence, this work had also the objective of observing the impacts of Financial Education, from the elaborated activities, in the discussions that would surface during the research, creating possibilities of financial decisions that may contribute to a better future. Those activities show how the idea of consumption is conceived, that is, in what circumstances the aspects of saving appear, what is the real necessity of acquiring goods, reutilize products, avoid wasting e preserve the environment. The Financial Education, more specifically the one directed towards children and teenagers, might give this public, future mindful consumers and influencers in their social circles, a level of knowledge that will hardly get lost throughout their lives once that will establish behavior and consumption patterns more and more suitable to them. In this aspect, this research follows the Action Research from Thiollent (2011), and shows characterizations of this theory when the activities are prepared aiming at allowing the students’ autonomy in the construction of the knowledge. Among the achieved results, its important to highlight the students’ answers from the perspective of the Theory of Didactical Situations directed to environmental preservation awareness for a close future.